Consuelo / par George Sand. - Sand, George, 1804-1876, author. (Tufts University. Tisch Library., 2016)
Nouvelle édition.; Volume 3 of 3.; 1 online resource (3 volumes); Electronic reproduction. Medford, MA : Tisch Library, Tufts University, 2015. Scanned by the Boston Library Consortium/Open Content Alliance as part of the BLC OCA Digitization Project from a copy at the Tisch Library, Tufts University.; Series: Collection Michel Lévy.